Cost-Benefit Analysis and the Democratic Ideal - Karine Nyborg; Inger Spangen (Statistics Norway, Research Department, 1997)
In traditional cost-benefit analyses of public projects, every citizen's willingness to pay for a project is given an equal weight. This is sometimes taken to imply that cost-benefit analysis is a democratic method for making public decisions, as opposed to, for example, political processes involving log-rolling and lobbying from interest groups. Politicians are frequently criticized for not putting enough emphasis on the cost-benefit analyses when making decisions. In this paper we discuss the extent to which using cost-benefit analysis to rank public projects is consistent with Dahl's (1989) criteria for democratic decision-making. We find several fundamental conflicts, both when cost-benefit analysis is used to provide final answers about projects' social desirability, and when used only as informational input to a political process. Our conclusions are illustrated using data from interviews with Norwegian politicians.
Keywords: A13; D61; D70; H43; 330; Democracy; cost-benefit analysis